Transcriptomics and metabolomics analyses reveal pollen abortion mechanism in alfalfa early stage male sterile lines - Cai, Huicai; Zhang, Shuhe; Yu, Weijie; Jia, Xue; Yu, Lan; Xu, Bo; Wang, Yingzhe (Frontiers in Plant Science, 2024)
This study investigates early-stage anther development in cytoplasmic male sterile (CMS) alfalfa lines (MSJN1A) in relation to the isotypic maintainer line (MSJN1B).Histological analyses revealed abnormal degradation of tapetal cells post-meiosis in the CMS line. Notably, during the early mononuclear stage, the central vacuoles in the microspores were absent, leading to evident pollen abortion. These findings suggest that pollen abortion in the CMS line is associated with the delayed disintegration of the tapetum and structural anomalies in microspore vacuoles. Non-targeted metabolome sequencing revealed 401 and 405 metabolites at late tetrad and early mononuclear stages of alfalfa, respectively. Among these, 39 metabolites were consistently upregulated, whereas 85 metabolites were downregulated. Differential analysis revealed 45 and 37 unique metabolites at each respective stage. These metabolites were primarily featured in pathways related to energy, phenylpropane, sucrose and starch, and fatty acid metabolism. Integrated analysis demonstrated that differentially expressed genes and differential metabolites were co-enriched in these pathways.Additionally, quantitative real-time PCR and physiological index analysis confirmed downregulation of key genes involved in anther development, illustrating that changes in upstream gene regulation could significantly impact downstream metabolite levels, ultimately influencing pollen fertility.